Fatigue of Clip Connectors for Offshore Drilling Risers under the Combined Influence of High Mean Stress and Biaxial Tension. (2015) - Gaur, Vidit; Doquet, Véronique; Persent, Emmanuel; Roguet, Eléonore
Abstract: Push-pull fatigue tests at various R ratios (σmin /σmax ), as well as combined cyclic tension and internal pressure tests with various proportions of each loading were run on a 2.5%Cr-1%Mo steel to investigate separately the effects of a mean stress and of positive stress biaxiality. Fatigue lives were found to decrease with increasing mean stress at fixed biaxiality and a non-linear effect of stress biaxiality on fatigue lives was observed at a fixed R ratio. The damage mechanisms were found to change with both parameters and these modifications were analyzed. Many popular multiaxial fatigue criteria were unable to describe all the data. Thus, a new fatigue criterion based on Gerber's parabola, has been proposed that captures the evolution of the endurance limit under the combined effect of mean stress and biaxial tension.